2020
DOI: 10.1002/adfm.202001196
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Polypeptide‐Protein Hydrogels for Promoting Infected Wound Healing

Abstract: Protein is the key composition of all tissues, which has also been widely used in tissue engineering due to its superior biocompatibility and low immunogenicity. However, natural protein usually lacks active functions such as vascularization, osteo‐induction, and neural differentiation, which limits its further applications as a functional biomaterial. Here, based on the mimetic extracellular matrix feature of bovine serum albumin, injectable polypeptide‐protein hydrogels with vascularization and antibacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 221 publications
(179 citation statements)
references
References 46 publications
3
168
0
Order By: Relevance
“…Biocompatibility Test: CCK-8 was employed to analyze the proliferation behavior of primary rat BMSCs (10 000 per well) on the scaffolds, which was performed according to the protocol provided by the Dojindo company. [43] In brief, the test reagent was mixed with fresh Dulbecco's Modified Eagle Medium (DMEM, Gibco) on day 1, 3, and 5 and incubated for 2 h at a constant incubator containing 5% CO 2 . Then the mixed solution absorbance was quantified by a microplate reader (Infinite F50, TECAN) at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Biocompatibility Test: CCK-8 was employed to analyze the proliferation behavior of primary rat BMSCs (10 000 per well) on the scaffolds, which was performed according to the protocol provided by the Dojindo company. [43] In brief, the test reagent was mixed with fresh Dulbecco's Modified Eagle Medium (DMEM, Gibco) on day 1, 3, and 5 and incubated for 2 h at a constant incubator containing 5% CO 2 . Then the mixed solution absorbance was quantified by a microplate reader (Infinite F50, TECAN) at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Silk-based materials have shown a promising capability to sustain Schwann cell growth for nerve repair [43]. Previously, it was also found that polyacrylamide hydrogel with a stable and clear surface groove structure of 30 µm pave the way for effectively guiding the cell growth of Schwann cells [22]. Therefore, the behavior of Schwann cells on both TPSF hydrogel and Topo@TPSF hydrogel with a groove width of 30 µm was investigated.…”
Section: Schwann Cell Behavior and Cytotoxicitymentioning
confidence: 99%
“…Biocompatible materials, such as collagen [17], silk [18], and chitosan [19], have great potential in biomedical applications [20]. These natural biopolymers have significant advantages, such as long-term safety [21], desirable biocompatibility [22], and biodegradability [23]. However, the weak mechanical strength of most biopolymer-based scaffolds goes against the formation of artificial topographic structures [24].…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the vascularization of vascular peptide, the 3D extracellular matrix characteristics of BSA protein and the rapid antibacterial ability of silver ions, the repair of infected wounds was promoted. In addition, hydrogels are also widely used in critical bone defects [ 152 ]. Yan et al prepared silk fibroin hydrogels with high cell adhesion function to repair bone defects by enhancing the osteogenic differentiation ability of bone marrow mesenchymal stem cells (BMSCs) [ 153 ].…”
Section: Application Of Bp- Based Hydrogel In Bone Regenerationmentioning
confidence: 99%